The Shafts of Strife and War: A Critical Analysis of the Immigration (Mass Arrivals) Amendment Bill - Foulkes, Christopher (Victoria University of Wellington Law Review, 2012)
This article critically analyses the Immigration (Mass Arrivals) Amendment Bill 2012 currently before Parliament, which purports to deal with the potential mass arrival by sea of asylum seekers. The article first sets the legislation in its domestic and international law context as well as empirically comparing the changes with those recently enacted in Canada and Australia. The purported purposes of the legislation are examined by the article and it is seen that each of these are fraught with legal difficulties. Four major substantive changes the Bill would introduce are then outlined. In relation to the purposes of the legislation, New Zealand's domestic and international legal framework, and in comparison with similar regimes in Australia and Canada, this article concludes that the proposed New Zealand legislation is questionable in terms of both purpose and likely efficacy.